2021
DOI: 10.1099/jmm.0.001421
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pH on growth of Staphylococcus epidermidis and Staphylococcus aureus in vitro

Abstract: The pH of skin is critical for skin health and resilience and plays a key role in controlling the skin microbiome. It has been well reported that under dysbiotic conditions such as atopic dermatitis (AD), eczema, etc. there are significant aberrations of skin pH, along with a higher level of Staphylococcus aureus compared to the commensal Staphylococcus epidermidis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
1
11
1
1
Order By: Relevance
“…This is not surprising, given the commensal nature of the 19N strain, and is in accordance with previous data, wherein S. epidermidis strains from B clonal lineage were shown to have higher growth rates when exposed to acidic pH ( Espadinha et al, 2019 ). However, our results contrast with those obtained by Iyer et al who observed that another S. epidermidis strain belonging to the A/C cluster ( S. epidermidis ATCC12228) was insensitive to increasing pH values (pH 5–7) ( Iyer et al, 2021 ). This discrepancy may be explained by the fact that the assays were performed with an A/C cluster strain, with distinct growth conditions: in that case the growth was performed in a microtiter plate.…”
Section: Discussioncontrasting
confidence: 99%
“…This is not surprising, given the commensal nature of the 19N strain, and is in accordance with previous data, wherein S. epidermidis strains from B clonal lineage were shown to have higher growth rates when exposed to acidic pH ( Espadinha et al, 2019 ). However, our results contrast with those obtained by Iyer et al who observed that another S. epidermidis strain belonging to the A/C cluster ( S. epidermidis ATCC12228) was insensitive to increasing pH values (pH 5–7) ( Iyer et al, 2021 ). This discrepancy may be explained by the fact that the assays were performed with an A/C cluster strain, with distinct growth conditions: in that case the growth was performed in a microtiter plate.…”
Section: Discussioncontrasting
confidence: 99%
“…Staphylococcus is the second most predominant genus in the sebaceous skin microbiome. Staphyloccocci, such as Staphylococcus aureus and Staphylococcus epidermis , are tolerant of the acidic pH found in oily skin and produce lipases to utilise the lipid-rich substrate of these sites [ 32 , 87 , 88 ]. Interestingly, the retroauricular crease is a sebaceous site with low phylotype richness that tends to remain temporally stable due to the prevalence of Cutibacterium [ 78 , 89 ].…”
Section: Skin Topography and The Microbiomementioning
confidence: 99%
“…The absence of coliform bacteria and fecal coliforms indicates the good quality of the investigated water, whereas determining the presence of Staphylococcus aureus ( S. aureus ) is not directed. A dependence of bacterial growth on pH value present in different matrices was shown in recent studies, with S. aureus having a more sensitive parameter to pH value than Staphylococcus epidermidis [ 3 ]. In 2005, a study described a dependency on the carbon dioxide (CO 2 ) concentration with the growth rate of S. aureus at an incubation temperature of 37 °C.…”
Section: Introductionmentioning
confidence: 99%